Pengaruh Kondisi Keuangan, Struktur Modal, Ukuran Perusahaan Dan Modal Kerja Terhadap Profitabilitas Pada Perusahaan Financial Di Bei Periode 2016 – 2019 - Jeselin Jeselin; Elly Tashia; Wenny Anggeresia Ginting (CERED Indonesia Institute, 2022)
Analyze the influence of financial conditions, capital structure, firm size and working capital onProfitability of Financial Companies on the IDX for the 2016 – 2019 period. The research approach used is a quantitative approach. The sampling method is purposive sampling, a sample of 46 financial companies on the Indonesia Stock Exchange for the period 2016 – 2019. The results show the debt to equity ratio, current ratio, ln total assets, and working capital have a simultaneous and significant effect on return on assets in financial companies. on the IDX for the period 2016 – 2019. Debt to equity ratio has an effect and partially significant to the return on assets of financial companies on the IDX for the 2016 – 2019 period. The current ratio has a partial and significant effect on the return on assets of financial companies on the IDX for the 2016 – 2019 period. Ln total assets have a partial and significant effect on the return on assets in Financial Companies on the IDX for the 2016 – 2019 period. Working capital has a partial and significant effect on the return on assets of Financial Companies on the IDX for the 2016 – 2019